Teaching English grammar through person-based aspects - PhD, docent Adash Eshankulovna Rustamova; Master, Guljahon Xoliyeva Farhod qizi (Zien Journals, 2023)
In some perspectives, the potential for identifying elements important to language learning through video games and Android applications is explored. It is crucial to approach language learning from a pragmatic perspective. To achieve the intended goals, innovations are used. The difficulties in the process of teaching English as a second language can be smoothed out by using the right approaches. Students' attention is piqued and their language learning skills are improved in a fun way when English is taught to them through video games and Android apps. This article describes the numerous difficulties that arise when teaching a language and offers workable solutions. The benefits of teaching languages through video games are outlined, including apps for Android.
Keywords: Technologies; Video game; Android apps; Second language learners